Prevalence of antimicrobial resistance, biofilm formation, efflux pump activity, and virulence capabilities in multi-drug-resistant Klebsiella pneumoniae isolated from freshwater fish farms - Kummari Suresh; Devika Pillai (IWA Publishing, 2024)
The present study aimed to determine the antibiotic resistance, underlying mechanisms, antibiotic residues, and virulence genes involved in 32 multi-drug-resistant Klebsiella pneumoniae isolates from freshwater fishes in Andhra Pradesh, India. Antibiogram studies revealed that all isolates were multi-drug-resistant, harbored tetA (96.8%), tetC (59.3%), tetD (71.9%), nfsA (59.3%), nfsB (53.1%), sul2 (68.7%), qnrC (43.7%), qnrD (50%), blaSHV (75%), blaTEM (68.7%), and blaCTX-M (93.7%) genes. Multiple antibiotic resistance index was calculated as 0.54. Sixteen isolates were confirmed to be hyper-virulent and harbored magA and rmpA genes. In total, 46.9, 31.2, and 21.9% of the isolates were categorized as strong, moderate, or weak biofilm formers, respectively. All isolates possessed an active efflux pump and harbored acrA, acrB, acrAB, and tolC genes in 94% of the isolates, followed by mdtK (56.2%). Porins such as ompK35 and ompK36 were detected in 59.3 and 62.5% of the isolates, respectively. Virulence genes fimH-1, mrkD, and entB were present in 84.3, 81.2, 87.5% of the isolates, respectively. These findings imply a potential threat that multi-drug-resistant bacterial pathogens could transmit to surrounding environments and humans through contaminated water and the aquaculture food chain. HIGHLIGHTS Multiple factors contribute to the emergence of MDR Klebsiella pneumoniae in aquaculture, raising concerns about public health hazards.; Hyper-virulent, antibiotics resistance, biofilm, efflux pump gene determinants were identified by PCR.; Findings suggest that a comprehensive multifaceted approach based on better management practices and biosecurity in aquaculture is essential.;